Understanding Cardiovascular Risk Perception Among Females Patients With Hypercholesterolemia And Their Risk Reduction Strategies - Samsudin, Suhaiza; Md Aris, Mohd Aznan; Abdullah, Fa`iza (International Journal of Psychosocial Rehabilitation, 2025)
Introduction: With the increasing trend of hypercholesterolemia in the Malaysian adult population over the past five years, cardiovascular disease (CVD) remains the leading cause of death and disability. However, only half of the public has recognised hypercholesterolemia as a risk factor for CVD. Therefore, an accurate perception of hypercholesterolemia and CVD risk factors by the patient itself is important as this is one of the factors that explain health-related behaviours. Methodology: A qualitative study was conducted to understand the patient perceptions of hypercholesterolemia and CVD risk factors, as well as the strategies to prevent CVD risk. It involved a total of 13 women with hypercholesterolemia detected in their blood during a routine medical screening at a primary health care clinic in the International Islamic University Malaysia, Kuantan, Pahang. The interviews were audio-recorded, transcribed, coded, and analysed using the NVivo version 12 software. Result: All participants showed their concern regarding hypercholesterolemia and were aware that a high level of cholesterol would adversely affect their health. They perceived themselves as at risk of developing CVD due to the high cholesterol level. However, they were unable to properly identify other CVD risks, while some were able to relate behavioural risk factors with CVD and discuss their lifestyle changes to prevent CVD. In contrast, a few individuals were still unable to practise good lifestyle habits despite their concerns. Conclusion: The finding of this study implied the need for proper education and communication with the physician-in-charge in terms of CVD risk in order to improve patient uptake of healthy lifestyle choices.